The Effectiveness of Using Collaborative Strategic Reading (CSR) on Students’ Reading Comprehension of Narrative Text - Narindia Lisandy; Nuryansyah Adijaya (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2019)
This study aimed to find out whether or not the use of collaborative strategic reading (CSR) will be effective on students’ reading comprehension of narrative text. The study used a quantitative method with pre-experimental design. The instruments used in this study were pre-test and post-test and the subjects of this study were the tenth-grade students of MA Annida Al-Islamy. The data were analyzed by using the t-test. The results showed that the students mean score in pre-test was 64 while in post-test mean score was 78. The result of this study analysis obtained 8.439 to and 2.045 tt with significant of 5%. Thus, it can be said that the use of collaborative strategic reading (CSR) on students’ reading comprehension of narrative text was effective.